Switch to a Novel Breeding Resource Influences Coexistence of Two Passerine Birds - Duckworth, Renée A.; Hallinger, Kelly K.; Hall, Nerissa; Potticary, Ahva L. (Frontiers in Ecology and Evolution, 2017)
A crucial step in adapting to urban habitat is switching to novel, often man-made, resources. Switching to a novel resource can influence the dynamics of species coexistence, particularly if it alters trade-offs in performance. While such switches are frequently documented, their influence on species coexistence has been difficult to assess because it requires knowledge of performance tradeoffs in the context of both historical and novel resource use. Western and mountain bluebirds provide a unique system in which to investigate the effects of a resource switch on species coexistence because both depend on secondary nest cavities to breed and, across a large part of their range, have switched to using man-made nest boxes. Western bluebirds are less dispersive, but more aggressive, than mountain bluebirds leading to a successional pattern of species replacement in many nest box populations; however, there is evidence of continued coexistence in natural post-fire habitat. Nest boxes differ from natural cavities in both distribution, which may affect the dynamics of interference competition between the species, and thermal conductance, which may impact competition by altering survival of ectothermic young. Here, we use a combination of experimental manipulations of nest box density and more than a decade of fitness and incubation temperature data to investigate whether altered resource distribution or thermal environment best explain patterns of species replacement in nest box populations. In both species, we found that females breeding in nest boxes were unable to maintain normal incubation temperatures during inclement weather and experienced similar offspring mortality patterns. Moreover, climatic variation across populations did not predict species’ relative abundance. Instead, experimental manipulation of nest box density showed that mountain bluebirds persisted longer when nest boxes were distributed further apart, suggesting that nest box distribution may be a key factor in understanding how human-created habitat impacts coexistence of bluebird species. These results emphasize that knowledge of species interactions in the historical habitat is crucial to understanding population dynamics as species transition to novel, man-made habitat.